Vision-based structural scaling factor and flexibility identification through mobile impact testing. (1st May 2019) - Tian, Yongding; Zhang, Jian; Yu, Shanshan
Highlights: A single camera is adopted for mobile impact testing of all substructures. The Gradient Hough Transform method is employed for calculating multipoint displacements. Mode shapes and flexibility matrix of the entire structure are identified. Abstract: Owing to the limited field of view (FOV) of a single camera, structural properties (i.e. mode shapes and flexibility matrix) of a large structure cannot be directly obtained from vision-based measurements. To address this issue, a mobile impact testing method with noncontact vision-based measurement was proposed in this article to identify mode shapes and flexibility matrix of the entire structure. The novelty of the proposed method lies in that it not only can improve the testing efficiency of bridge structures by measuring structural multipoint displacements with a single camera, but also can identify more structural properties from mobile impact testing data. In the proposed method, measurements of the entire structure are divided into a number of setups by moving a single camera, from which multipoint dynamic displacements of each setup are calculated by gradient-based Hough Transform (GHT) method using image sequences acquired from the camera. After that, structural mode shapes and flexibility matrix of the entire structure are identified by integrating impacting forces and dynamic displacements of all measurement setups. Finally, a laboratory cantilever beam was designed to verify the proposed method, the results obtained from the proposed method agree well with reference values, which has successfully verified the effectiveness of the proposed method.